Defect configuration of ceria for Pt anchoring toward efficient methanol oxidation. (22nd March 2023) - Xu, Guodong; Ye, Zihao; Zou, Keqian; Li, Chuanfu; Zhou, Dejun; Lv, Rongguan; Huang, Bing; Li, Jing; Cai, Weiwei
Abstract: As a potential next-generation power source for portable electronic devices, commercialization process of direct methanol fuel cell (DMFC) technology is hindered by the high dependence of anode methanol oxidation reaction (MOR) on precious Pt catalyst. In order to improve the efficiency of Pt toward MOR catalysis, a Ni doping strategy is proposed for defect engineering on ceria substrate to achieve uniform dispersion of Pt nanoparticles. Besides, Ni could also act as electron donor for Pt and hence favor the removal of CO intermediate on Pt and act as a co-catalyst toward MOR. Superior MOR activity and great stability is therefore achieved for the as-prepared Pt/CeO2 @Ni catalyst with 3 times higher peak MOR current density compared with Pt/C catalyst. Due to the evenly anchored Pt and enhanced CO oxidation ability caused from Ni doped ceria substrate, Pt utilization of the Pt/CeO2 @Ni catalyst is calculated to be 3.24 times higher than that of the commercial Pt/C catalyst. By considering the significantly improved stability, the Pt/CeO2 @Ni catalyst has the potential for application in DMFC devices. Highlights: Ni doping strategy is proposed for defect engineering on ceria for uniform Pt anchoring. Ni could act as electron acceptor from Pt and hence favor the removal of CO. Pt utilization is therefore 3.73 times enhanced compared with commercial Pt/C.